The Effect Of Work Environment And Leadership On Employee Job Satisfaction At Al-Kahfi Super Kitchen Bengkulu - Alfaruq, Abdullah Azam; Anggriani, Ida; E G, Ida Ayu Made (Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study aims to determine the effect of work environment and leadership on employee job satisfaction at Al-Kahfi Super Kitchen Bengkulu, both partially and simultaneously. Data collection methods used questionnaires with a sample size of 35 people. The analysis methods used were validity testing, reliability testing, multiple linear regression, coefficient of determination, F-test, and t-test. Based on the results of the study and discussion, it was found that the work environment had a significant effect on employee job satisfaction at Al-Kahfi Super Kitchen Bengkulu because the significance value was 0.000 < 0.05, and leadership had a significant effect on employee job satisfaction at Al-Kahfi Super Kitchen Bengkulu because the significance value was 0.001 < 0.05. The work environment and leadership simultaneously have a significant effect on employee job satisfaction at Al-Kahfi Super Kitchen Bengkulu because the significance value is 0.000 < 0.05.